Impact of lineage-specific epidermal growth factor receptor mutations in cancer - Amy Rios; Kimberly A. Jorge; Gizelle G. Ramirez; Chester A. Thompson; Tikvah K. Hayes (Philosophical Transactions of the Royal Society B: Biological Sciences, 2026)
Abstract The epidermal growth factor receptor, or EGFR, is one of the most frequently altered oncogenes in human cancer and is a critical therapeutic target. EGFR alterations span a broad spectrum, including gene amplification, point mutations, truncations, in-frame insertions or deletions, and fusions, yet their mutational distribution is cancer type-specific. This distribution impacts the effectiveness of EGFR-targeted therapies across EGFR-mutant cancers. This review will cover what is currently known about the EGFR-driven cancer landscape in the following cell lineages: lung, brain, colon, breast and bladder. This article is part of the discussion meeting issue ‘Epidermal growth factor receptor after 40 years’.